A study of the possibilities of using linseed flour and rice husk fiber as an additional source of raw materials in the bakery industry - Zilikha Moldakulova (PC Technology Center, 2021)
The paper is devoted to solving the problem of the nutritional and biological value of rye-wheat bread by enriching it with non-traditional local plants raw materials – linseed flour and rice husk fiber. Rice husks are rarely used in bakery production, and in most cases remain unprocessed. However, this research defined the right ways for using them and set as a preliminary work in this field. The study has been carried out in two stages: firstly, linseed flour was added to the rye-wheat bread recipe in an amount of 5; 10; 15; 20 % to the weight of wheat flour. Secondly, dietary fiber was added to these experimental samples, prepared from rice husks without removing amorphous silicon dioxide in an amount of 0.3; 0.5; 0.7 % to the total mass of rye-wheat flour. The optimization of the ratios of the flour components with a simplex-lattice design was carried out and the rheological measurements of dough and bread were conducted on the farinograph and Chopin alveograph.